2001
DOI: 10.1074/jbc.m010478200
|View full text |Cite
|
Sign up to set email alerts
|

A Vertebrate Aldo-keto Reductase Active with Retinoids and Ethanol

Abstract: Enzymes of the short chain and medium chain dehydrogenase/reductase families have been demonstrated to participate in the oxidoreduction of ethanol and retinoids. Mammals and amphibians contain, in the upper digestive tract mucosa, alcohol dehydrogenases of the medium chain dehydrogenase/reductase family, active with ethanol and retinol. In the present work, we searched for a similar enzyme in an avian species (Gallus domesticus). We found that chicken does not contain the homologous enzyme from the medium cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0
1

Year Published

2001
2001
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 61 publications
4
29
0
1
Order By: Relevance
“…Competitor RNA was added to multiple RT-PCR reactions, generally 6 -8, such that the copy number added ranged from 0.5 ϫ 10 6 to 0.025 ϫ 10 6 . PCR products were then separated by agarose gel electrophoresis.…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Competitor RNA was added to multiple RT-PCR reactions, generally 6 -8, such that the copy number added ranged from 0.5 ϫ 10 6 to 0.025 ϫ 10 6 . PCR products were then separated by agarose gel electrophoresis.…”
Section: Rt-pcrmentioning
confidence: 99%
“…ADH7 has been described only in the chicken embryo, and showed activity with retinoids. ADH8 has been described in amphibians and has a tissue distribution and substrate specificity similar to mammalian ADH4 (6). Previously, only one class of ADH has been described in fish, which are structurally similar to mammalian ADH3 and functionally similar to ADH1 (7,8).…”
mentioning
confidence: 98%
“…Several enzymes capable of catalyzing the first step of RA synthesis, oxidation of retinol to retinal, have been identified within the alcohol dehydrogenase (ADH) and short-chain dehydrogenase/reductase (SDR) families (1), plus there exists a recently identified cytosolic form that is a member of the aldoketo reductase family (13). The human and mouse ADH families each contain five classes of cytosolic enzymes (14) encoded by a tight cluster of genes tandemly organized in the same transcriptional orientation on chromosome 4 (human) or chromosome 3 (mouse) (15).…”
mentioning
confidence: 99%
“…However, the initial sequence data suggested that the novel ADH was of a third family type, AKR [1], previously not known to represent ADH or retinal reductase activities, but rather aldehyde and aldose reductases [7]. This chicken protein was characterized by a combination of protein and cDNA sequence analysis, correlated with model building and enzymatic analysis, which yielded information on all segments of the primary structure except the N-terminal part [1]. To verify the new structure, and to establish the nature of the blocked, chemically modified N terminus, two-dimensional (2-D) gel electrophoresis combined with tan-…”
mentioning
confidence: 99%
“…In cases with novel mechanisms, multiple forms, or special contaminants, protein isolation may be difficult and analysis may start without pure material. One such case was encountered during a recent definition of an aldo-keto reductase (AKR) as an alcohol dehydrogenase (ADH) with retinal reductase activity in chicken tissues [1]. Usually, vertebrate ADHs are of the mediumchain dehydrogenase/reductase (MDR) zinc-containing protein type [2,3].…”
mentioning
confidence: 99%